The female voice in Brazilian society - Silva, Aldemiza Correia da (2022)
Considering that the female voice was not heard in the social environment, until then, as a result of the patriarchal and religious domain, this study aims to promote the discussion about the female voice in different social spheres, as well as in the political environment, since that representation is of paramount importance so that disadvantaged groups can expose their needs and legitimize their struggles. Being, therefore, a work of qualitative nature, it is a bibliographic review, which brought as a basis for the theoretical discussion the authors Vedana (2022), Casanova (2022), Sousa (2000), Natansohn, Brunet and Paz (2011), Abrantes (2018) among others that corroborate the ideas presented here. As a conclusion, it can be noted that despite the evolution in women's freedom of expression, especially with the advent of the internet, a lot of commitment and social policies are still needed to develop girls' empowerment and boys' sense of equality.